Application of Dual-loop Robust Control on a Two-wheeled Robot with Varying slip - He, Tianyi (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, 2021)
In this paper, a dual-loop scheme of robust control is applied to control the Two-Wheeled Robot (TWR) subject to varying slip conditions. The slip between the wheel and ground is modeled as the disturbance perturbing the nominal model. The dual-loop control has separate design for optimal nominal performance and robust performance. The robustness is guaranteed and the better performance is achieved by 'online' adaption to varying slip conditions. Simulation results demonstrate that the dual-loop control scheme can extend the stability region than LQG control and achieve improved performance than the mixed H_{2}/H_{∞} control. In the experiment, a small size TWR is placed on different surfaces and controlled by dual-loop control and LQG control. Experimental results validate that the dual-loop control scheme outperforms the classical LQG control and mixed H_{2}/H_{∞} control.